2014
DOI: 10.9755/ejfa.v26i10.18503
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic, grain morphological and locality variation in rice phytate content and phytase activity

Abstract: Phytate complexes in whole grain rice are indigestible by human but can be broken down by endogenous phytase enzyme. The inherent phytate content and phytase activity could influence the nutritional quality of whole grain rice. This work aims to determine and identify their variability with genotypes, growing areas and grain morphology. It was found that the whole rice grain was largely high in phytate content (18.20 to 32.36 g/kg) but low in phytase activity (4.77 to 102.65 U/kg), with significant variation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…These samples are generally referred to Bario rice cultivars in this study, due to potential distribution of the original Bario rice from the Bario highlands. Genotypic and grain morphological information of these rice cultivars were obtained from previous study (Lee et al 2014). Rice bran colors ( Fig.…”
Section: Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…These samples are generally referred to Bario rice cultivars in this study, due to potential distribution of the original Bario rice from the Bario highlands. Genotypic and grain morphological information of these rice cultivars were obtained from previous study (Lee et al 2014). Rice bran colors ( Fig.…”
Section: Samplesmentioning
confidence: 99%
“…Bario rice cultivars collected from Bario highlands are a good source of protein and thiamine, moderate in glycemic index and also low in fat content (Nicholas et al 2014). Nevertheless, no information is available on the bioaccessibility of nutrients and antioxidant properties of Bario rice cultivars in relation to their high phytic acid content (18.20 to 32.36 g/kg) (Lee et al 2014). Nutrient bioaccessibility refers to the nutrient fraction released from the food matrix, in contrast to nutrient bioavailability that refers to nutrients available for utilization under physiological conditions (Parada and Aguilera 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Ficco et al (2009) using the principal component analysis and the Pearson's correlation found a negative association of P i and TGW (-0.31 p < 0.01) and of P i and YLD (-0.27 p < 0.05) in durum wheat, while similar findings were confirmed by other studies (Monasterio and . According to Lee at al. (2014) phytase activity affecting the PA content in wheat appeared to be determined by the grain length to width ratio.…”
Section: Correlation Analysismentioning
confidence: 99%